2013
DOI: 10.4103/1119-3077.110133
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge attitude and practice regarding diabetes and diabetic retinopathy among the final year medical students of King Faisal University Medical College of Al Hasa region of Saudi Arabia: A cross sectional survey

Abstract: This survey highlights some of the lacuna in the teaching system of the medical students and identified the need for improvement in their knowledge, attitude and practices for treating the patients with diabetes and diabetic retinopathy. This can be done by incorporating special syllabus focusing on diabetes and diabetic retinopathy in their teaching programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 0 publications
3
28
3
Order By: Relevance
“…Three studies investigated students' knowledge of the treatment of cardiovascular diseases 38, 87, 88. Two studies reported deficiencies in students' knowledge of diabetes mellitus therapy – specifically, diabetic retinopathy and insulin treatment 38, 87.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies investigated students' knowledge of the treatment of cardiovascular diseases 38, 87, 88. Two studies reported deficiencies in students' knowledge of diabetes mellitus therapy – specifically, diabetic retinopathy and insulin treatment 38, 87.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported deficiencies in students' knowledge of diabetes mellitus therapy – specifically, diabetic retinopathy and insulin treatment 38, 87. Rehman et al .…”
Section: Resultsmentioning
confidence: 99%
“…20 It is observed in P17 that, although aware of the necessary changes in their life habits for proper control of the disease, these are not incorporated into their daily lives. In this specific case, the behavior in question is related to the frustration resulting from a complication of DM2, which is retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has an overall global prevalence of 34.6%. 2 Diabetic retinopathy accounts for 4.8% of cases of blindness, throughout world. 3 Diabetes is characterized by increased blood sugar levels.…”
Section: Introductionmentioning
confidence: 99%